Fiscal Adjustment in Greece under the Financial Rescue Programme : The Distributional Effects on Greek Households - Sugawara, Naotaka (Taylor and Francis, 2013)
This article examines the distributional effects of the fiscal adjustment programme in Greece agreed with the European Commission (EC) and the International Monetary Fund (IMF) in 2010. It deals with adjustment measures that are front loaded and directly related to the household welfare: an increase in Value-Added Tax (VAT) and excise rates and a reduction in wages and pensions. Analysing these two effects reveals that the programme decreases the welfare of all households in Greece but that the adverse effects of the adjustment are mitigated in favour of the poor.